Topological Origin of the Super‐Flexible Phase of Se and Se‐Rich Glasses and Aging‐Induced 5‐fold Narrowing of Glass Transition Width. Issue 1 (10th November 2021) - Chbeir, Ralph; Welton, Aaron; Boolchand, Punit
Abstract : Pure Se glass and ternary A x B y Se1− x − y glasses where A = Ge and B = P or As, in the low mean coordination number, ⟨ r ⟩, range of 2.00 < ⟨ r ⟩ < 2.12 display a 3‐ to 5‐fold reduction in the width of the glass transition when aged at room temperature over 4–8 months. Group IV (Ge) and group V (P, As) additives serve to crosslink the base Se glass polymeric chains, Se n, with n  > 250 atoms and to reduce the length " n " between cross‐link points as x and y are increased. Herein, it is shown that in such weakly crosslinked glasses, the continued narrowing of the glass transition width T g by a factor of 3–5, as in pure Se, stems from the fact that polymeric Se n chain segments between the crosslink points continue to have a length n of at least eight atoms or more. Such polymeric Se n chains are super‐flexible and reconstruct with each, as in pure Se, promoting structural ordering responsible for T g narrowing. When n  < 8, super flexibility is steadily lost. Along with the flexible, intermediate, and stressed‐rigid phases, a new super‐flexible phase of Se and Se‐rich glasses is obtained. Abstract : Pure Se and Se‐rich glasses can exist in a new topological phase called the super‐flexible phase. In this phase, polymeric Se n chains exist in the 250 >  n  > 8 length range. Glass transition widths of such glasses can narrow by a factor of 3–5 upon room temperature aging for 4 months as the long Se n chains reconstruct.